Cerebrospinal Fluid HIV-1 Compartmentalization in a Patient With AIDS and Acute Varicella-Zoster Virus Meningomyeloradiculitis - Falcone, E. Liana (Oxford University Press, 2013)
We report a case of AIDS presenting as varicella-zoster virus (VZV) meningomyeloradiculitis associated with human immunodeficiency virus (HIV) quasispecies compartmentalization within the cerebrospinal fluid (CSF), and a CSF viral load that was 1 log higher than in peripheral blood. Prolonged antiviral therapy for both VZV and HIV type 1 was associated with partial resolution.